2003
DOI: 10.1016/s0168-8278(03)80497-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating pro-brain natriuretic peptide (PROBNP) and brain natriuretic peptide (BNP) in patients with cirrhosis. Relation to cardiovascular dysfunction and severity of disease

Abstract: Background and aims: Cardiac dysfunction may be present in patients with cirrhosis. This study was undertaken to relate plasma concentrations of cardiac peptides reflecting early ventricular dysfunction (pro-brain natriuretic peptide (proBNP) and brain natriuretic peptide (BNP)) to markers of severity of liver disease, cardiac dysfunction, and hyperdynamic circulation in patients with cirrhosis. Patients and methods: Circulating levels of proBNP and BNP were determined in 51 cirrhotic patients during a haemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 46 publications
9
86
1
9
Order By: Relevance
“…Moreover, these correlate with the stage of the liver disease and may show the severity of myocardial dysfunction and ventricular hypertrophy. Despite these favorable features BNP and pro-BNP may not be able to indicate the hyperdynamic circulation [56,57]. These biomarkers have also been shown to be helpful in the screening of CCM [58].…”
Section: Laboratory Markersmentioning
confidence: 99%
“…Moreover, these correlate with the stage of the liver disease and may show the severity of myocardial dysfunction and ventricular hypertrophy. Despite these favorable features BNP and pro-BNP may not be able to indicate the hyperdynamic circulation [56,57]. These biomarkers have also been shown to be helpful in the screening of CCM [58].…”
Section: Laboratory Markersmentioning
confidence: 99%
“…Abbreviations: IVRT, isovolumic relaxation time, which is the time period during which the mitral and aortic valves are both closed. The left ventricle begins to relax, but before left ventricular filling occurs; DDT, diastolic deceleration time, which is the time period from the peak of the early diastolic filling velocity to the end of the E wave cardiomyopathy as the cause of this electrophysiological abnormality [26].…”
Section: Electrophysiological Abnormalitiesmentioning
confidence: 99%
“…Henriksen and colleagues [26] found that both pro-BNP (a propeptide of BNP) and BNP elevations correlated with the severity of cirrhosis as well as the degree of cardiac dysfunction. Yildiz et al [30] also reported a significant correlation between the BNP levels and the Child-Pugh score.…”
Section: Serum Markersmentioning
confidence: 99%
“…Ventricles become an important source of NPs, particularly Brain-Type Natriuretic Peptide (BNP) in response to myocardial ischaemia and stretch by volume and pressure overload [6]. N-terminal-proBNP (NT-proBNP) resulting from cleavage of ProBNP (a precursor of BNP) is more stable with longer half-life, it has been shown to be superior in predicting morbidity and mortality or hospitalization for chronic heart failure and an even better indicator of early cardiac dysfunction than BNP [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed increased NP concentrations in patients with cirrhosis suggesting cardiac dysfunction [8,10,11]. However, few studies had demonstrated NP significance in prognosis of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%